Combinatorial Optimization and Applications A Tribute to Bernard Gendron - Crainic, Teodor Gabriel; Gendreau, Michel; Frangioni, Antonio (International Series in Operations Research & Management Science, 2024)
XIII, 506 p. 63 illus., 46 illus. in color.